Meralgia paresthetica Solving the diagnostic dilemma (International Journal of Biomedical Research, 2018)
Meralgia paraesthetica (MP) is a clinical syndrome produced by entrapment mono-neuropathy of lateral femoral cutaneous nerve (LFCN). It classically presents as numbness, paresthesia or dysesthesia of anterolateral aspect of thigh but sometime it may mimic conditions like lumbar radiculopathy, femoro-acetabular impingement, trochanteric bursitis, etc. Since it has wide spectrum of clinical presentation, it should be the diagnosis of exclusion when causes of anterolateral thigh pain is not explained by other known causes. The aim of this review is to provide an overview of this clinical condition with the emphasis on various clinical presentations and anatomical variations of the lateral femoral cutaneous nerve. Different methods of diagnosis and treatment are also explored and discussed in this paper.